The Phenomena of Criminal Acts in Environmental Pollution by Corporations - Hartanto (Journal of Legal and Cultural Analytics, 2023)
The problem of environmental pollution is increasingly in the spotlight and global. The system adopted in criminal law on environmental pollution is a system of criminal responsibility based on mistakes. Corporate crime can emerge along with the advancement of economic development. Corporate crime is not new, but something that has happened frequently and alternated from time to time. Currently, corporations are included in the category of legal subjects so that they can be subject to criminal and civil sanctions. The doctrinal legal research used has the aim of analyzing environmental regulations associated with corporations that pollute. UU no. 32/2009 Protection and Management of the Environment as a legal umbrella mentions the environment as a unitary space with all objects, styles, conditions, and organisms, including humans and their behavior that affect nature itself, survival, livelihoods and welfare of humans and other living things. Losses from environmental pollution are not only in one area but can spread to the surrounding area with a fantastic total value of losses. environment for sustainable development. It was concluded that corporations as perpetrators of criminal acts of corruption in environmental pollution cases, must receive stricter laws than at present, considering that the impact of this corruption is quite large and also causes large costs to repair damaged environmental returns, not to mention if it is associated with environmental damage. social.